Tinjauan Yuridis Tentang Reksa Dana Syariah Sebagai Alternatif Investasi bagi Investor (Lex Jurnalica, 2010)
General meaning of the Mutual Fund Sharia (Islamic Infestment Fund) are not much different from the meaning of Mutual Funds in general. What distinguishes Conventional Mutual Funds Mutual Funds with Shariah lies in its operation, in which the Fund uses the provisions of sharia principles. Mutual Funds in Sharia principles used in the form of contract between owners of capital (rab al-mal) and the Investment Manager (amyl), selection and implementation of investment transactions, and in determining the distribution of results. Islamic Investment Fund is an agency that helps intermediaris surplus units do placements and to invest. One of the objectives of Shariah Fund is to meet the needs of investors who want to earn investment income from a source and a clean and accountable religiously, and in line with Sharia principles. Based on the background have been described, it is at issue is: How does the comparison of Mutual Funds and Mutual Funds Conventional Syariah? How forms of execution of the agreement (contract) in the mechanism of Sharia investment through mutual funds? How is legal protection for investors in Shariah investments through Mutual Funds? The method used in this paper is Normative research methods, with data collection in literature (Library Reseach). In this study, data collection method adopted by the authors is to use a technique reviewers of the sources of data have been obtained and related to the research problem. The study documents (library materials) data collection undertaken by the author is through the written record. By way of seeking data about things or variables such as notes, transcripts, books, newspapers, etc., that there is room library Â Keywords: Juridist, Reksa Dana, Syariah